О гельминтофауне страуса нанду (Rhea americana L.) в заповеднике Аскания-Нова - Смогоржевская, Л.А.; Корнюшин, В.В.; Бевольская, М.В. (Вестник зоологии, 1970)
Была исследована гельмиитофауна нанду, акклиматизированных в заповеднике Аскания-Нова. Выявлено три вида гельминтов, два из которых—Chapmania tauricollis (Chapman , 1876) и Dicheilonema rheae (Owen , 1843)—специфичные паразиты нанду и один — Dispharynx nasuta (R u d., 1819)—обычный паразит домашних и диких куриных. The given article deals with preliminary results of studying the helminthofauna of Rhea americana L. acclimatized in the Askaniya-Nova reservation. All four investigated nestlings at the age of 2—2.5 months proved to be infected with helminths. Three species of helminths are detected, two of which — cestode Chapmania tauricollis (Chapman , 1876) and nematode Dicheilonema rheae (Owen , 1843)—are specific parasites of R, americana L. C. tauricollis was known previously only in South America. Nematode Diepharynx nasuta (R u d,, 1819) is a usual parasite of domestic and wild Qalliformes, in R. americana it is registered for the first time. A loss of /oung birds is observed because of helminthosis, evoked by these parasites.